2019
DOI: 10.3847/1538-4357/ab1eb1
|View full text |Cite
|
Sign up to set email alerts
|

The Host-galaxy Properties of Type 1 versus Type 2 Active Galactic Nuclei

Abstract: The unified model of active galactic nuclei (AGNs) proposes that different AGN optical spectral types are caused by different viewing angles with respect to an obscuring "torus". Therefore, this model predicts that type 1 and type 2 AGNs should have similar host-galaxy properties. We investigate this prediction with 2463 X-ray selected AGNs in the COSMOS field. We divide our sample into type 1 and type 2 AGNs based on their spectra, morphologies, and variability. We derive their host-galaxy stellar masses (M )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
95
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 103 publications
22
95
2
Order By: Relevance
“…Figure 11 shows that type-I AGNs have smaller M * than type 2 AGNs and that their SFRs are similar. The different M * is also in agreement with Zou et al (2019) and indicates that dust in the host galaxy may contribute to the optical obscuration of AGNs. Since there are fewer type-I AGNs in our sample, such results may also be biased.…”
Section: Host Galaxy Properties Of Different Agn Typessupporting
confidence: 81%
See 2 more Smart Citations
“…Figure 11 shows that type-I AGNs have smaller M * than type 2 AGNs and that their SFRs are similar. The different M * is also in agreement with Zou et al (2019) and indicates that dust in the host galaxy may contribute to the optical obscuration of AGNs. Since there are fewer type-I AGNs in our sample, such results may also be biased.…”
Section: Host Galaxy Properties Of Different Agn Typessupporting
confidence: 81%
“…The simple AGN unified model considers that the different types of AGNs should be attributed to different viewing angles and thus predicts that their host galaxy properties should be similar. However, some studies have suggested that their host galaxy properties were not exactly similar (Bornancini & García Lambas 2018;Zou et al 2019). Zou et al (2019) The fraction of optically obscured AGNs is plotted versus the X-ray luminosity of 5 bins (log L X <42.5; 42.5<log L X <43; 43<log L X <43.5; 43.5<log L X <44; log L X >44 ).…”
Section: Host Galaxy Properties Of Different Agn Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The model assumes that the central engine is surrounded by a dusty torus (i.e. the AGN unified model; Antonucci 1993;Urry & Padovani 1995;Netzer 2015;Zou et al 2019). The torus absorbs a fraction of the UV and optical emission from the central engine and reemits the energy as IR photons.…”
Section: Introductionmentioning
confidence: 99%
“…In the last several decades, many works have focused on the study of active galactic nuclei (AGNs) (Dressler et al 1985;Miller et al 2003;Krumpe et al 2012;Enoki et al 2014;Kagaya et al 2017;Chen et al 2018;Liu et al 2019;Zou et al 2019). Dressler et al (1985) and Miller et al (2003) explored the correlation between the presence of AGNs and the local environment of AGN host galaxies.…”
mentioning
confidence: 99%